Factors that impact achievement and persistence of students in developmental courses receiving Pell Grants at the rural community college - Davis Dietz, Pamela Michelle (Kansas State University, 2011)
A growing body of literature suggested that students who come from poverty have potential risk factors that included: being the first in the family to attend a college, being poorly prepared for the academic rigors of college and requiring remedial developmental coursework. Students from poverty who accessed the rural community college also struggled with rising tuition and fees, as well as the cost of books. Students from poverty had greater struggles with social and personal issues and experienced lower completion rates. Limited research has been conducted with this segment of rural students from poverty backgrounds attending community college in the rural setting. This dissertation described a phenomenological case study approach to identify the impact of poverty on the achievement and persistence of rural students who access the rural community college. A small community college in the Midwest representing a rural population and a high percentage of poverty students was selected as the site for the study. The goal of this research was to explore perceived factors by students receiving Pell Grants and in developmental courses while in attendance at a rural community college in order to identify possible strategies to ameliorate barriers in their rural community college experience. The research found this student population to be at high risk with multiple risk factors. In addition to being developmental and receiving Pell Grants, other scholarships combined with working part-time and often full-time were needed to supplement student finances; poor high school academic preparation and counseling; lacked the computer skills necessary for college coursework; being non-traditional; lack of consistency in tutoring services; and being food short and hungry. These additional risk factors made this segment of the student population fragile.
Keywords: Developmental; Pell Grants; Rural community college; Education, Community College (0275)